Examining the impact of social media usage on start-ups performance: Mediating role of brand image - Emmanuel Bruce; Zhao Shurong; John Amoah; Sulemana Bankuoru Egala; Philip Adu Sarfo; Bernard Ekow Baidoo; Dennis Akomanyi Darko; Luo Ailing; Ynag Yongxing (PLoS ONE, 2025)
Social media has emerged as an assertive communication and brand-building tool in the dynamic entrepreneurship landscape. This study explores the influence of social media usage on the performance of start-ups, focusing on the mediating role of brand image. The research employs a quantitative approach, collecting data from 450 start-ups in Ghana through surveys. Data collected was processed and analyzed through PLS-SEM. The findings of the study supported all the formulated hypotheses. The outcome suggests that, social media, brand image and innovation capabilities all have direct and positive linked with startup performance. Additionally, the findings proved a mediating role of brand image between social media usage and startup performance. Understanding the dynamics between social media, brand image, and performance is vital for start-ups seeking to thrive in competitive markets. Based on the outcomes in the findings, the study recommends social media marketing tool for startup businesses in Ghana to stern competition and drive sustenance. This research contributes to academic literature and practical insights, offering nuanced perspectives on leveraging social media as a strategic tool for cultivating a brand image and influencing overall start-up performance. The implications of the study findings serve as guideline for startups and young entrepreneurs’ in developing countries as they develop their marketing strategies.